A Novel 6,8,9-Trisubstituted Purine Analogue Drives Breast Cancer Luminal A Subtype MCF-7 to Apoptosis and Senescence through Hsp70 Inhibition - Kul, Pinar; Tuncbilek, Meral; Ergul, Mustafa; Yenilmez Tunoglu, Ezgi Nurdan; Tutar, Yusuf (Anti-Cancer Agents in Medicinal Chemistry, 2023)
Background: Cancer cells restrain apoptotic and senescence pathways through intracellular heat shock protein 70 (Hsp 70). These cells aid stimulus-independent growth, and their higher metabolism rate requires Hsps. Hsps compensate abnormally increased substrate protein folding rate of cancer cells. Objective: Misfolding of substrate proteins especially signaling substrate proteins, may not function properly. Therefore, Hsp70 folds these substrate proteins into their native-fully functional states, and this mode of action helps cancer cell survival. Methods: Targeting Hsps is promising cancer therapy, and in this study, 6,8,9-trisubstituted purine derivatives were designed and synthesized to inhibit Hsp70 and drive cancer cells to apoptosis. Further, oncogenic stimuli through inhibitors can induce an irreversible senescent state and senescence is a barrier to transformation. Results: Hsp70 helps cancer cells to bypass the cellular senescence program, however, binding of N6-(4- isopropylaniline) analogue (7) depletes Hsp70 function as evidenced by aggregation assay and Hsp70 depletion induces senescence pathway. Conclusion: The purine-based inhibitor-compound 7 effectively inhibits MCF-7 cell line. Moreover, the therapeutic potential with regard to the senescence-associated secretory phenotype has complementary action. Dual action of the inhibitor not only drives the cells to apoptosis but also force the cells to be in the senescence state and provides promising results specially for luminal A type breast cancer therapy.
Keywords: cytotoxic activity